Numerical and experimental analysis of a novel heat pump driven sorption storage heater - Aydin, Devrim; Casey, Sean P.; Chen, Xiangjie; Riffat, Saffa (Elsevier Sci Ltd, 2018)
This study investigates a hybrid solid sorption heat storage/air sourced heat pump system for energy efficient heating of buildings. The proposed system could convert excess energy generated using photovoltaic panels/off-peak electricity to heat and charge the sorption material to store that heat for later use. The novel heat recovery process employed in the system enables high heat storage efficiency through condensation of desorbed moisture in a heat storage charging cycle. In this study five different sorbents were tested in a novel prototype system. Four sorbents were salt based composites (SIM's) and one was Zeolite 13X. According to the results, the coefficient of performance (COP) of the system varied in the range of 1-2 for short-term operation (where t < 240 min) depending on the sorption material properties and system operating conditions. The overall performance of the prototype sorption storage heater was determined through long cycle testing. The system provided approximate to 6.8 kWh thermal energy output with a sorbent volume, Vs = 0.04 m(3) (over a 1200 min discharge time), corresponding to an energy density, E-d = 170 kWh/m(3). The required charging duration, to desorb the moisture was experimentally determined as 360 min. Based on the total energy input output for both charging and discharging processes, the COPs was calculated at 2.39. According to the analysis, the experimental results were found in good agreement with the numerical simulation.
Keywords: SIM; Heat pump; Sorption heat storage; Composite adsorbent; Heating; Numerical and experimental analyses